High-sensitive Troponin T in asymptomatic aortic stenosis. (25th November 2020) - Hadziselimovic, E; Greve, A.M; Sajadieh, A; Olsen, M.H; Kesaniemi, Y.A; Nienaber, C.A; Ray, S.G; Rosseboe, A.B; Willenheimer, R; Wachtell, K; Nielsen, O.W
Abstract: Background: High-sensitive cardiac Troponin T (hsTnT) is the most frequently used biomarker for the detection of cardiomyocyte injury. Severe aortic stenosis (AS) leads to an increased left ventricular load, with the potential of myocardial injury reflected by increased TnT levels. However, there is a lack of studies showing the prevalence and prognostic role of elevated hsTnT in patients with asymptomatic AS. Purpose: To examine the association between the hsTnT levels and AS severity in asymptomatic AS patients. We hypothesized that patients with more severe AS will have elevated hsTnT levels and that hsTnT levels are associated with a higher risk for aortic valve events (AVE) and all-cause mortality (ACM). Methods: We performed a post-hoc analysis in 1739 asymptomatic patients with mild to moderate-severe AS, enrolled in the randomized, double-blinded SEAS-study (Simvastatin and Ezetimibe in Aortic Stenosis). All patients had available hsTnT blood samples measured at baseline (Year 0) and Year 1. We defined moderate to severe (mod-severe) AS as a transaortic maximal outflow velocity (Vmax)>3.5 m/s combined with aortic valve area (AVA)<1.0 cm 2, otherwise non-severe AS. An hsTnT>14 ng/L was high according to assay (Roche, Elecsys Troponin T hs on cobas e 601). Linear multivariable regression model examined the association of hsTnT levels to clinical and echocardiographic variables. Cox multivariable regression model evaluated competing risks and hazard ratios (HR) of outcomes while adjusting for relevant variables, including a Framingham 10-years risk score of cardiovascular diseases. The competing risks were either ACM or AVE, i.e. the first of AVR, cardiovascular death and heart failure due to AS progression. Results: At baseline, hsTnT was high in 26% (453/1739) patients; 25% (380/1529) in non-severe and 35% (73/210) in mod-severe AS. Relative TnT change over one year was 17% (mean 1.17, SD 1.01); 15% in non-severe vs. 32% in mod-severe AS, and neither associated to AS severity, hsTnT at baseline or lipid-lowering treatment. In multivariable linear regression analysis, there were significant correlations between hsTnT at baseline and age, male gender, creatinine, left ventricular mass index and BMI (all p<0.001, R-square=0.42), but not with AS severity. In multivariable Cox regression analyses, a high hsTnT at baseline was associated with AVE 1.61 [95% CI 1.29–1.99]. In contrast, hsTnT at baseline was not associated to all-cause mortality (see figure). Conclusions: In asymptomatic AS patients without severe AS, high-sensitive Troponin T is not associated with AS severity in cross-sectional analyses, and its levels do not change substantially during one year of follow-up. However, patients with hsTnT >14 ng/l had a sixty percent higher independent risk of subsequent aortic valve events. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Acknowledgements: Main sponsor (SEAS): MSD Singapore Company, LLC, partnership between Merck & Co. Inc. and Schering-Plough Corporation. Blood analysis sponsor: Roche